Daniel Defoe and the representation of personal identity - Borsing, Christopher (Trinity College (Dublin, Ireland). School of English, 2012)
This thesis explores Daniel Defoe's treatment of the concept of personal identity as a literary construction and as a social fiction. An active contributor to the burgeoning print market of early eighteenthcentury England, Defoe capitalizes on popular taste but he also alerts readers to issues of textual credibility. His provocative destabilization of any fixed definition or image of a personal identity is at the heart of the thesis.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin.